Engaging Students in Class Research to Improve Their Learning Experience - Johnson, Hannah; Carroll, Zechariah; Omotajo, Damilola; Choudhary, Madhusudan (IJRDO- Journal of Educational Research, 2016)
Students enrolled in introductory genetics courses often arrive with a vague understanding of core genetic principles and concepts. Specifically, the wild-type phenotype, defined as the most common phenotype within a population, is often mistaken as the dominant phenotype. Presented here is a research-based activity that engages students in data collection and analysis while challenging them to eschew misconceptions concerning general principles. The protocols described here can be implemented in classrooms, teaching laboratories, or recitation sessions to elucidate these concepts across sub-disciplines such as cell biology, genetics, molecular biology, and microbiology.